2010
DOI: 10.2516/ogst/2009085
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Characterization of Geological Sites able to Host a Pilot-Scale CO2Storage in the Paris Basin (GéoCarbone-PICOREF)

Abstract: Résumé -Choix et caractérisation de sites géologiques propices à l'installation d'un pilote pour le stockage de CO 2 dans le bassin de Paris (GéoCarbone-PICOREF) -Le projet GéoCarbone-PICOREF avait pour objectif de caractériser des sites propices à la réalisation d'un pilote national de stockage du CO 2 en réservoir géologique perméable. Deux types de réservoir ont été examinés : des aquifères profonds, et des gisements d'hydrocarbures en voie d'épuisement. Les sites devaient être choisis de manière que le pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[2] Over the last decade, numerous studies have been undertaken to understand the physics that govern the transport of supercritical CO 2 in the subsurface and its subsequent trapping or leakage in the context of geological carbon sequestration [Bachu and Adams, 2003;Birkholzer et al, 2009;Brosse et al, 2010;Burton et al, 2008;Celia et al, 2011;Doughty and Pruess, 2004;Grimstad et al, 2009;Nogues et al, 2012;Pawar et al, 2009;Pruess et al, 2003]. All of these studies have considered static material properties, such as permeability and porosity, for geologic formations and leakage pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Over the last decade, numerous studies have been undertaken to understand the physics that govern the transport of supercritical CO 2 in the subsurface and its subsequent trapping or leakage in the context of geological carbon sequestration [Bachu and Adams, 2003;Birkholzer et al, 2009;Brosse et al, 2010;Burton et al, 2008;Celia et al, 2011;Doughty and Pruess, 2004;Grimstad et al, 2009;Nogues et al, 2012;Pawar et al, 2009;Pruess et al, 2003]. All of these studies have considered static material properties, such as permeability and porosity, for geologic formations and leakage pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The permeability field had a log-normal distribution (Table 2), and 99 % of values lay between 0.31 mD and 3.16 D (consistent with local data for the Dogger aquifer (e.g., Delmas et al 2010;Rohmer and Seyedi 2010;Brosse et al 2010;Casteleyn et al 2010;Lopez et al 2010;Rojas et al 1989)). Stochastic simulations were applied on an initial fine and regular mesh (cell size of 7*7*7 m).…”
Section: Modeling Of Permeability Fieldsmentioning
confidence: 69%
“…This reservoir was also selected by the French geological survey (BRGM) as a potential target for CO 2 geological storage. 1 However, several studies concerning both type of exploitations showed that the Oolithe Blanche forms a complex carbonate reservoir presenting heterogeneous petrophysical and microstructural properties. [2][3][4][5][6] Many studies using P-wave velocities measurements have shown that dynamic moduli of carbonate rocks are controlled by several microstructural parameters such as rock fabric, pore type and shape, porosity and pore fluid, making it difficult to attribute changes in seismic expression to any one parameter.…”
Section: Introductionmentioning
confidence: 99%